Die Baukunst des 13. Jahrhunderts in Österreich - Schwarz, Mario (2013)
This book is the first complete description of 13th century architecture in Austria. This period was significant for ist political and historical events and upheavels in the provinces of Austria, but at the same time for the transition from romanic to gothic style. The book is the result of the author's continuous studies in this field of architectural history for more than 35 years. Basing on his doctoral thesis of 1975 the author is outlining a completely new panorama of the development in 13th century architecture by using the results of recent investigations, reconstructions and newly interpreted historical sources. Some important results were achieved on behalf of FWF-projects under the author's direction (reconstruction of the Capella Speciosa at Klosterneuburg, research on the history of the Imperial Palace di Vienna). The results are corresponding in perfect way with the scientifical researches in neighbouring countries as Czech Republic, Hungary, Slovenia and Germany, in regard of the long range cultural communications during the Middle Ages, which in former theories were denied by presupposing a distinct stylistic retard in Austrian architecture. Highly important was the author's proof that in the 13th century in Austria existed a contemporaneity between advanced and retarded stylistic forms. The choice of the stylistic attitude mainly depended on the client. The introduction of the book gives a survey of the actual state of research, followed by three chapters, which explicate the conditions in the 12th century, differentiated geographically (alpine regions, Danube valley) and concerning the clientage (dukes, archbishops and bishops of Salzburg and Passau) as well. By this way the general tendencies and motives (Cistercian architecture of Heiligenkreuz and Zwettl; Patavian architecture at Göttweig, Kremsmünster, Vienna, St.Pölten, Tulln; architecture at Salzburg - cathedral of archbisphop Konrad III - Gurk, Seckau, Hartberg) are outlined, which dominated the further development. In the following first main part, which is describing the first half of 13th century, the important role of the Austrian sovereigns (duke Leopold VI and duke Friedrich II) as founders and benefactors of eminent church architecture is emphasized. With these works of art most actual influences of french gothic architecture came to Austria (Capella Speciosa at Klosterneuburg, cloisters at Lilienfeld and Heiligenkreuz). The quarrel in ecclesiastical policy between the Babenberg dukes of Austria and the bishops of Passau, concerning the plan to establich a further diocesy in Austria, caused a competition in the field of architecture between the two powers. Thus the bishops of Passau reconstructed their patronage churches (St.Pölten, Kremsmünster, Ardagger) in Austria in a sumptuous way. Besides this stylistically advanced architecture there existed also a building acitivity not to be neglected, which was supported by the lower aristocracy and the duke's officials, who also founded some monasteries and churches. These buildings were constructed by local workmen, who were following the traditional patterns of late romanic style (Baumgartenberg, Wilhering, Bad Deutsch Altenburg, Petronell). At the dawn of the Babenberg dynasty an important political intervention of emperor Friedrich II. von Hohenstaufen took place. Recent researches indicate that the reconstruction of St.Stephen's church in Vienna with the famous "Riesentor" with sculptural decorations in Norman Style was initiated by the emperor, even as the foundation of the castle at the place of the later Imperial Palace, which obviously followed the type of the emperor's fortresses in Sicily. In spite of the political agitations and upheavals in the middle of the century some remarkable works of architecture were created, as the castle of Starhemberg, the fortresses at the border to Hungary (Wienertor at Hainburg), St.Virgil's chapel at Vienna and the charnel house at Tulln), where different in